A SUBJECTIVE WELL-BEING EVALUATION OF PUBLIC TRANSPORT USERS DURING TRAVEL AND ACTIVITIES: APPLICATION OF DAY RECONSTRUCTION METHOD (DRM) CONCEPT - Winny Novalina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
The question regarding daily travel and activities implication to individuals’ well-being was heavily debated from past decades. This research is motivated by relationship between travel, activity, and well-being, specifically for public transport users. The modification of day reconstruction method applied in data collection to capture the changes of personal preference during travel and activities. The one day travel activities survey questionnaire distributed to public transport user in Bandar Lampung. Furthermore, 420 samples distribute based on sampling criteria which the result of survey evaluated based on completeness and variance. Key findings of this study are in line with the past study of well-being yet found some crucial findings. It is found that subjective well-being preference is changes during period of time when moving from activity to another activity. Furthermore, this papers also found that majority of individuals have negative experience on their daily travel.